KONSEPSI ULAMA DALAM ALQURAN - Andi Muhammad Akmal (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The Messenger of Allah was uswatun hasanah (good example). On the other hand, the Ulama are heirs of the Prophets. The existence of scholars in human life is very urgent and principled. That they are problem solving for all the problems of the people. The task, function and role of the Ulama in human activities is heavy, because it is a mandate, but it is very noble in its position. Allah swt. inform in Al Qur'anul Karim about the existence of Ulama. The accentuation can be seen from the nature, the form of the use of Ulama, Ulama categories and features according to the Qur'an. This matter, will be studied through interpretation approach maudhuiy (thematic interpretation)